A global-local approach for the elastoplastic analysis of compact and thin-walled structures via refined models. (15th August 2018) - Petrolo, M.; Nagaraj, M.H.; Kaleel, I.; Carrera, E.
Highlights: This paper presents a novel global-local approach based on advanced structural theories. The results focus on elastoplastic analyses of thin-walled structures. The computational efficiency and accuracy of the framework is the main outcome of the paper. The present formulation leads to a twofold reduction in the number of degrees of freedom. Abstract: A computationally efficient framework has been developed for the elastoplastic analysis of compact and thin-walled structures using a combination of global-local techniques and refined beam models. The theory of the Carrera Unified Formulation (CUF) and its application to physically nonlinear problems are discussed. Higher-order models derived using Taylor and Lagrange expansions have been used to model the structure, and the elastoplastic behavior is described by a von Mises constitutive model with isotropic work hardening. Comparisons are made between classical and higher-order models regarding the deformations in the nonlinear regime, which highlight the capabilities of the latter in accurately predicting the elastoplastic behavior. The concept of global-local analysis is introduced, and two versions are presented - the first where physical nonlinearity is considered for both the global and local analyses, and the second where nonlinearity is considered only for the local analysis. The second version results in reasonably accurate results compared to a full 3D finite element analysis, with a twofold reduction in the number of degrees of freedom.